The integration of rural development research and community service - Uphoff, Norman (University of the Free State, 2005)
English: The integration of community service and research is an important subject especially in South Africa, where academics are called upon by the government and the public to contribute to more rapid and equitable development and, particularly for purposes of this contribution, rural development. The generation and application of knowledge should go hand in hand because the process of applying knowledge to real-world situations can itself provide productive challenges and venues for adding to the body of available knowledge. Those concerned with advancing science should appreciate that the knowledge gained in this way has been validated, under realistic conditions, which render the generated knowledge more reliable and relevant.

Afrikaans: Die integrasie van gemeenskapsdiens en navorsing is ’n belangrike onderwerp, veral in Suid-Afrika, waar die regering en die publiek ’n beroep op akademici doen vir vin- niger en billiker ontwikkeling. Vir die doeleindes van hierdie bydrae raak dit lande- like ontwikkeling in die besonder. Die voortbrenging en toepassing van kennis moet hand aan hand gaan omdat die proses waardeur kennis op werklike situasies van toe- passing gemaak word, op sigself produktiewe uitdagings en terreine bied vir die toe- voeging tot die beskikbare kennisinhoud. Diegene wat gemoeid is met die bevordering van die wetenskap, sal waardering hê vir die feit dat die geldigheid van die kennis wat op hierdie wyse verkry word, in realistiese omstandighede bevestig is en die gegene- reerde kennis daarom meer betroubaar en meer relevant maak.
Keywords: Rural development; Community service; Research